International encyclopedia of the stock market - Sheimo, Michael D., 1944-; Loizou, Andreas; Fitzroy Dearborn Publishers (Chicago : Fitzroy Dearborn Publishers, 1999)
"The first major work of its kind to discuss international stock markets, this encyclopedia is essential for anyone interested in investing in today's global markets. Because of the increasing globalization of businesses, American investors can no longer limit themselves to information about the U.S. stock market. These two volumes define over 2,000 terms dealing with the history and practices of international stock markets in industrialized as well as developing countries, and discuss individuals, institutions (such as banks, brokerage and leveraged buyout firms), events, and slang terms relating to stock markets. The readable entries provide accurate, up-to-date information of interest to the burgeoning number of private and professional investors. This work is a valuable addition to school, public, and academic library collections."--"Outstanding reference sources 2000", American Libraries, May 2000. Comp. by the Reference Sources Committee, RUSA, ALA.
v. 1. A through L -- v. 2. M through Z.
Includes bibliographical references and indexes.
Keywords: Stock exchanges -- Encyclopedias